2012
DOI: 10.1007/s12223-011-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of vinasse for the production of polyhydroxybutyrate by Haloarcula marismortui

Abstract: Vinasse, a recalcitrant waste of the ethanol industry was employed for the production of polyhydroxyalkanoate (PHA) by the extremely halophilic archaeon, Haloarcula marismortui in shake flasks. The PHA was recovered by osmotic lysis of the cells and subsequent purification by sodium hypochlorite and organic solvents. Through UV-vis spectroscopy, differential scanning calorimetry, Fourier transform infrared, and nuclear magnetic resonance spectroscopy, the PHA was found to have characteristics very similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 26 publications
3
40
1
5
Order By: Relevance
“…One hundred milliliters raw vinasse was adjusted to pH 2.0 and treated with 5.0 g activated carbon (AC) as described in Pramanik et al ([2012]). The AC was removed by centrifugation, the supernatant filtered, neutralized with NaOH/HCl as required and the filtrate characterized as mentioned in the sub-section, “Analytical Methods”.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred milliliters raw vinasse was adjusted to pH 2.0 and treated with 5.0 g activated carbon (AC) as described in Pramanik et al ([2012]). The AC was removed by centrifugation, the supernatant filtered, neutralized with NaOH/HCl as required and the filtrate characterized as mentioned in the sub-section, “Analytical Methods”.…”
Section: Methodsmentioning
confidence: 99%
“…Petri plates were prepared containing the growth medium (GM) as suggested by DSMZ, composed of (g/l) NaCl 200.0; MgSO 4 .7H 2 O 20.0; KCl 2.0; casamino acids 5.0; yeast extract 5.0; C 5 H 8 NNaO 4 1.0; Na 3 C 6 H 5 O 7 3.0; FeCl 2 .4H 2 O 0.036; MnCl 2 .4H 2 O 0.00036; pH 7.0-7.2, swabbed with H. mediterranei culture containing 10 8  CFU/ml and further evaluated as described in Pramanik et al ([2012]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC1, including at concentrations where growth of other microorganisms is usually inhibited. Pramanik et al (2012), e.g., reported on the inhibitory effects of vinasse on the growth of the bacterium Haloarcula marismortui at concentrations above 10%. Omar et al (2002) found that nitrogenfixing bacterial strains such as Azospirillum brasiliense, Bacillus polymyxa, and Azotobacter chroococcum were only able to utilize concentrations of 6e15% of vinasse obtained from an Egyptian distillery.…”
Section: Effect Of Ph Vinasse Concentration and Incubation Time On mentioning
confidence: 99%
“…Assim como o residual de material orgânico, ao final do cultivo ainda havia ART disponível no meio, como mostrado na Figura 2 (b). Pramanik et al (2012) utilizaram vinhaça para a produção de P(3HB) a partir de Haloarcula marismortui, um microrganismo halofílico (capaz de crescer em elevadas concentrações de sais) e o acúmulo final de P(3HB) em meio contendo 10 % (v/v) de vinhaça foi de 30 % (m/m) com μ Xrmax de 0,086 h -1 . É importante ressaltar que, apesar do acúmulo de P(3HB) do cultivo apresentado neste trabalho, com estratégia de pulso e limitação em nitrogênio assim como para os autores citados, ter ficado em torno de 30 %, este trabalho utilizou um microrganismo não halofílico e as concentrações de vinhaça avaliadas foram superiores (até 100 %), demonstrando que a bactéria abordada neste estudo, apesar de não ser um microrganismo halofílico, foi capaz de crescer e produzir P(3HB) em meio de cultivo contendo elevadas concentrações de vinhaça.…”
Section: Ensaios Para Analisar O Crescimento E Produção De P(3hb) Porunclassified